Parameters which affect the stiffness of bitumen and bituminous hot mixes - Kulo?lu, N. (My University, 2001)
This paper deals with bitumen and bituminous mixes, using suitable mathematical models that take into account the parameters affecting their elastic and plastic stiffnesses. These parameters are stress level and acting time, penetration index, softening time and temperature. Viscosity and the total acting time of the load affect the elastic stiffness of bitumen. The elastic stiffness of bitumen and the voluminous concentration of the aggregate influence the elastic stiffness of the mix. The plastic stiffness of the mix is directly dependent on the plastic stiffness of bitumen. The most important parameter affecting the elastic as well as plastic stiffness of bitumen and bitumen mixes is the difference between the softening point and the temperature. For this reason, the quality of bitumen must be determined with respect to the maximum and minimum temperatures in the region to prevent damage surfacing over time.
Bitüm ve bitüml-dsu sicak karisi?mlarin rijitlig?ne etki eden parametreler
Keywords: Bitumen; Bituminous Mixes; Parameters; Stiffness